THE EFFECT OF APPLYING GROUP INVESTIGATION METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Asrul, Nurmahyuni; Amaniarsih, Dwi Suci; Juliana, Juliana (Universitas Suryakancana, 2021)
The purpose of this study was to determine whether the Group Investigation method had a significant effect on student achievement in writing descriptive texts. This research is quantitative by conducting an experimental design. The population used in this study was students of X SMK Shandy Putra 2 Medan. The sample of this study was randomly selected by taking 25 students for the experimental and control classes. Advertisement Pre-test Post-test is given to determine student scores. The score was calculated using the t-test formula. The results showed that the value of t-observation (2.44)> t-table (2.01) with df (48), meaning that the Group Investigation Method can improve student achievement in writing descriptive texts. So, the researcher concludes that there is a significant effect of the Group Investigation Method on student achievement in writing descriptive texts. And finally, the researcher gives suggestions to apply the method, especially the Group Investigation Method because it will have a significant influence on student achievement in writing descriptive texts. Keywords: Descriptive Text, Group Investigation.